Modelling auditor supplied non-audit services : do industry specialist premia exist? - Wong, J. (Research paper series (University of Melbourne. Dept. of Accounting), 2001)
This paper models the fees generated by Big 6 auditors from their listed company audit clients in respect of non-audit services (NAS). While the factors that affect the variability of audit fees are well researched, the factors underlying NAS fees, also supplied by audit firms, are not well understood. This study argues that while some factors that explain audit fees also explain NAS fees, there are also differences. In addition, this study proposes and tests for the existence of NAS industry specialist supplier premiums. The results show that company size and leverage are both highly significant explanators of NAS fees and considerable industry differences are also found. NAS industry specialization, as measured by market share also significantly explains NAS fees with a premium accruing to industry specialist NAS providers. Proxies for the type of NAS that might be demanded (consulting services relating to company health and taxation advice relating to the tax position of the company) were also significant in some circumstances.